Mastering Python : networking and security - Messier, Ric (Infinite Skills, 2014)
"In this Mastering Python - Networking and Security training course, expert author Ric Messier teaches you how to script with Python. This course is designed for users that are looking to extend their skillset with scripting. No experience is required, although any programming knowledge would be an asset. You will start with an overview of Python, including how to create and run scripts, use threads, and handle exceptions. From there, Ric will teach you how to network, including how to use the Python libraries for network scripting and develop basic scripts with network functionality. This video tutorial will also cover HTTP programming, security scripting, and forensic scripting. Finally, you will learn about Twisted Python, including the Echo server and HTTP client. "--Resource description page.